Biomass for Energy Application - Herak, David (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book focuses on the utilization of biomass for energy applications and mainly covers the original research and studies related to thermochemical conversion, biological conversion and physical conversion. It contains a summary the current scientific knowledge in the field of biomass utilization, which is the first of its kind in the literature. Energy potentials and different principles of energy transformation from various renewable energy sources (bamboo, wood residue, straw, sorrel, hay, pines, sunflower stalks, hazelnut husks, quinoa, camelina, crambe, safflower, muscantus and municipal sewage sludge, among others) are described in detail in this book. Different types of pyrolysis or torrefaction processing, combustion, thermal degradation, mechanical properties affecting processing, pre-treatment or treatment processes, or other processes based on thermochemical methods are described as well. The integral part of this book is the bibliometric analysis of worldwide publication trends on biomass and bioenergy with respect to the research evolution with the possibility of predicting future scenarios and the participation of stakeholders in the sector.